ABUDANCE OF MICRO DAN MACROZOOBENTOS IN PEAT POND GIVEN BIOFERTILIZER DOSES DIFFERENTATIONS - Adelia Renata; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACK            The research was conducted from 27 September to 27 Oktober 2018 in the Kualu Nenas village, Tambang subdistrict, Kampar Regency, Riau Province. The aim of this research was to find out abudance of micro dan macrozoobentos in peat pond given biofertilizer dosis differentations. Method of this research is an experimental method using a Complete Random Design (CRD) with one factor, five treatments, and four replications is P0 (control/ non biofertilizer), P1 (doses 700 g biofertilizer formulations/m2), P2 (doses 750 g biofertilizer formulations/m2), P3 (doses 800 g biofertilizer formulations/m2), P4 (doses 850 g biofertilizer formulations/m2). Result of this research that the best of treatment was P2 (doses 750 g biofertilizer formulations/m2) showed the 46.410 Ind/m2 of microzoobentos  and the macrozoobentos abundance was the best on the P2 with is 37.740 Ind/m2.Kata Kunci: Biofertilizer, Microzoobentos, Macrozoobentos, Abundance of                                Microzoobentos and Abundance of Macrozoobentos